ANTIMICROBIAL PROPERTIES OF CARBON NANOTUBE: A SUCCINCT ASSESSMENT - Ikhazuagbe Hilary Ifijen1*, Selina Ilunakan Omonmhenle2 (university of eloued جامعة الوادي, 2024)
Carbon nanotubes (CNTs) particularly single walled carbon nanotubes (SWNT) have been used in pharmacy and medicine for drug delivery systems in therapeutics since the beginning of the twenty-first century. Because carbon nanotubes have demonstrated the ability to transport a wide range of chemicals across membranes and into living cells, they have piqued interest in medicinal applications such as improved imaging, antimicrobial agents, tissue regeneration, and medication or gene delivery. Despite the abundance of evidence demonstrating the benefits of CNTs in terms of higher efficacy and fewer side effects, numerous recent studies have revealed unanticipated toxicities caused by CNTs. CNTs have recently gained a lot of attention for their antibacterial properties. The antimicrobial properties of carbon nanotubes, as well as their toxicity, are summarized and discussed in this mini review.
Keywords: Carbon nanotubes; antibacterial; toxicity.